Trypanosoma cruzi in Bats (Chiroptera; Mammalia) from the Brazilian Atlantic Forest, São Paulo State - França, Danilo Alves de [UNESP]; Louro, Mariana; Zúquete, Sara; Zanini, Dayane da Silva [UNESP]; Moraes, Gustavo Nunes de [UNESP]; Rocha, Gabrielle dos Santos [UNESP]; Biondo, Leandro Meneguelli; Fornazari, Felipe [UNESP]; Menozzi, Benedito Donizete [UNESP]; Fonseca, Isabel Pereira da; Langoni, Helio [UNESP] (MDPI, 2024)
The causative agent of Chagas disease is Trypanosoma cruzi, which is widely distributed throughout the South American continent and extends into North America. Its occurrence in bats is poorly described and may impact the disease’s maintenance and epidemiology. The aim of this study was to detect the agent by PCR assays targeting kDNA and nuclear DNA in the organs of 203 urban bats and rural vampire bats from the Brazilian Atlantic Forest, São Paulo state, during the pandemic period from 2020 to 2022. In total, 6 of the 203 bats (2.97%) were positive for T. cruzi. Infection was detected in 2% (2/101) of Desmodus rotundus, 33% (1/3) of Nyctinomops laticaudatus, 25% (1/4) of Artibeus lituratus, 4% (1/24) of Eumops glaucinus and in 2% (1/41) of Molossus molossus. The gene sequences obtained were assessed for quality and deposited in a public repository. Fruit bats were statistically associated with positivity for T. cruzi. To our knowledge, this study detected T. cruzi for the first time in bats from São Paulo state and in N. laticaudatus and E. glaucinus species.
Keywords: emerging disease; molecular epidemiology; PCR; phylogeny; urban bats; vampire bats